The politics of the right : socialist register 2016 - Panitch, Leo; Albo, Gregory (Socialist register, 2015)
Today the Left faces new challenges from political forces amassing on the radical right. The 52nd volume of the Socialist Register presents a serious calibration and a careful political mapping of these forces. It addresses pivotal questions on the reordering of the new right. These essays - very broad in terms of themes and places - speak to the global challenges the new right poses for the left at this historical moment.